Influence of Ni doping on PtNi nanoparticles: Synthesis, electronic/atomic structure and photocatalyst investigations - Varshney, Mayora; Sharma, Aditya; Shin, Hyun-Joon; Lee, Hyun Hwi; Jeon, Tae-Yeol; Lee, Byeong-Hyeon; Chae, Keun-Hwa; Won, Sung Ok (PERGAMON-ELSEVIER SCIENCE LTD, 2017)
Carbon-supported Pt and PtNi nanoparticles (NPs) were synthesized using a borohydride reduction method. Structural properties were studied by synchrotron X-ray diffraction (XRD) and the size/shape of the NPs was determined by transmission electron microscope (TEM). X-ray absorption spectroscopy with its two amendments; X-ray absorption near edge structure (XANES) and extended X-ray absorption fine structure (EXAFS), has been employed to investigate the local electronic/atomic structure surrounding the Pt and Ni atoms. XANES results, at Pt L-3-edge and Ni K-edge, have shown fractional oxidation of Pt and Ni atoms. The Pt3Ni1NPs have exhibited a lower bond distance of Pt Ni shell and higher coordination number of Pt Ni shells, indicating the alloy formation between Pt and Ni. We further have demonstrated that the Pt and PtNi NPs can serve as effective photocatalysts towards the degradation of water pollutant dye (methyl orange (MO)). By considering the interband charge transfer of Pt (5d -> 6sp), a tentative mechanism is proposed to understand the photocatalytic degradation of MO dye molecules by Pt/PtNi NPs under the light irradiation.